Unique Patient Identifier for National Ehealthcare Service Delivery: The Indian Approach - Palanivelrajan, P; Alli, P (International Journal of Computer Sciences and Engineering, 2025)
The main objective of the present day eHealthcare is the integrated, interfaced health information systems or networks that should be able to gather, parse, and ensemble the different parts of the medical record pertained to a patient without involving any risk of linking those of another patient. Identifying the multiple fragmented pieces of a specific individual patient data existing in disparate distributed systems for the purposes of exchange remains a challenge though appears to be easy to reach. Many of the countries adopting HL7 family of standards prescribe the Social Security Number or an equivalent or any demographic data of a patient as the Unique Patient Identifier as a data element in the PID division of the EHR. Tagging the distributed data sets with mere numbering needs additional information to confirm the identity of an individual patient and involves many risks. Aadhaar Number concept proves to be a best fix as the UPI. The present paper discusses the related facets to the concept of UPI and the relevance of the Indian Aadhaar Number